Divine, yet vulnerable: Gregory Nazianzen's human eikon - Thomas, G.R. (2017)
This thesis examines Gregory Nazianzen’s approach to the human eikon, vis à vis the imago Dei. In the following pages I challenge the popular view amongst scholars that Gregory presents the human eikon solely as the soul or the spiritual intellect. Rather, I argue that Gregory’s vision of the human eikon extends much further than this, embracing the full complexity and mystery of human existence.